42. WAITING TIME FOR OUTPATIENT EXAMINATION AND SOME INFLUENCING FACTORS AT THE EXAMINATION DEPARTMENT, KY ANH GENERAL HOSPITAL, HA TINH IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: 1) Determine the waiting time for medical examination of outpatients at the Examination Department, Ky Anh General Hospital, Ha Tinh in 2024. 2) Analyze some factors affecting the waiting time for medical examination of outpatients at the Examination Department, Ky Anh General Hospital, Ha Tinh, in 2024.Research method: Cross-sectional study combining quantitative and qualitative, conducted on 220 patients and hospital medical staff. Descriptive statistics and analysis methods were applied together with the T-test, Anova test, and the statistical significance threshold was p
Keywords: Waiting time for medical examination